Bangkitan Tegangan Listrik pada Rekayasa Piezoelektrik Berbasis Bahan Dapur - Alya Puspita Zahra; Muhammad Ikhsan Bachrul Alam; Regina Bilqis Wardani; Muhammad Sholeh; Atin Nuryadin; Lambang Subagiyo (Kappa Journal, 2024)
Piezoelectric constituents consist of PbZrTiO3 or PZT which contains lead (Pb) hich is industrial waste which is hazardous if it enters the human body. Based on this, the researchers used environmentally friendly kitchen materials in the form of Potassium Bitartrate and Sodium Bicarbonate as a substitute for the original piezoelectric material. Through the experimental method of mixing the two materials, the evaporation and refrigeration methods, amorphous solid forms were obtained. The solid is then coated with aluminum and tested for suitability by measuring the stress of the material before and after being vibrated. The voltage obtained after being vibrated formed an exponential graph with the highest voltage of 0.28 V. Then, the material was tested again for its feasibility in charging the capacitor and the voltage generated by the capacitor was obtained at. 0.0221V. Basic knowledge related to cross-curricular and subject-specific sustainability.